Hubungan Motivasi dengan Minat Lanjutan Pendidikan Ke Jenjang DIII Farmasi Siswa SMK Kesehatan Mutiara Insani Kota Tangerang - Sri Haryanto (STIKes Kharisma Persada, 2019)
Health as an element of general welfare must be realized in accordance with the ideals of the Indonesian people as referred to in the opening of the 1945 Constitution. Health development is directed towards the achievement of awareness, willingness and ability to live a healthy life for each population in order to realize optimal health status. The pharmaceutical profession as an integral part of the health system can be a key factor in the success of health services in health centers / hospitals. The purpose of this study was to identify the factors associated with further interest in continuing education in the DIII Pharmacy level at Mutiara Insani Health Vocational School Students in Tangerang City. This research is a quantitative study, using analytic survey research methods with cross sectional approach. The number of samples obtained was 26 students of class X. The results of this study indicate that there is a significant relationship between intrinsic motivation and interest in continuing education to the level of DIII Pharmacy (P value = 0.046), there is a significant relationship between extrinsic motivation and interest in continuing education to the level of education DIII Pharmacy (P value = 0.001), and there is no significant relationship between urged motivation and interest in continuing education to the level of DIII Pharmacy (P value = 1,000).